Analysis of Factors Influencing Young Voters in the 2024 Bengkulu Province Regional Head Election: A Quantitative Study Using Chi-Square and Fisher Exact Test Approaches - Sonia, Gita; Wanti, Novelisa Syendra; Damayanti, Putri; M. Zidan Mezilano Y; Sunandi, Etis (Journal of Statistics and Data Science, 2024)
Political participation of young voters has a strategic role in local democracy. This research aims to analyze the factors inhibiting young voters' participation in the 2024 Bengkulu regional election using Chi-Square analysis. This descriptive-analytic quantitative research involved 124 respondents aged 17-29 in the 2024 Bengkulu regional election, analyzing four variables: political knowledge, psychological factors, social environment, and technical constraints. Using the Fisher Exact test, the results showed no significant relationship between the variables and the voting decision. Interestingly, the participation rate of young voters is quite high, indicating the complexity of the dynamics of political participation of the younger generation. The research findings provide a new perspective on the dynamics of young voters' political participation, providing a foundation for the development of strategies to increase young people's political engagement in future elections.